DEPICTION OF STRUGGLE BY MIRANDA TO REACH LUCIA AGAINST MENTAL ILLNESS IN EVERYTHING HERE IS BEAUTIFUL - Fattamubina, Afifah Zakia; Prastiwi, Yeny (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2022)
This research discusses Miranda’s struggle to reach Lucia against mental illness in the novel Everything Here Is Beautiful. Everything Here Is Beautiful novel deals with an issue that is closely related to the individual's role in the extent to which the individual will or must go for the sake of the family. In this novel, Miranda, the older sister of her younger sister, Lucia, who suffers from mental illness, decides to step up to struggle for Lucia against her mental illness. Hence, in this research, the researcher examines Miranda’s struggle to reach Lucia against mental illness. The purpose of this research is to discover struggles by Miranda. This is descriptive qualitative research with an individual psychological approach as the theory. Individual psychological approaches rely on Alfred Adler's